(untitled) (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Producing products that customers want, pricing them correctly and developing well designed promotional plans are necessary but not sufficient conditions for customer satisfaction. The final part of the Jigsaw is distribution, the place element of the Marketing Mix. Products need to be available in adequate quantities, in convenient locations and at the time when customers want to buy them. Producers need to consider not only the needs of their ultimate customers but also the requirements of channel intermediaries, those organizations responsible for facilitating the distribution of products to customers. When producers and channel members are independent, inevitably conflict occurs from time to time. The intensity of conflict can range from occasional, minor disagreements that are quickly forgotten, to major disputes that fuel continuous bitter relationships. This paper focused on the challenges of channel conflicts management in soft drink industry with particular reference to coca-cola. The paper x-rayed the channels of distribution, generally and specifically in coca-cola; causes of channel conflicts and conflict resolutions. Recommendations were made on how best channel conflicts could be resolved through partnership approach, market partitioning, co-operation and adoption of super ordinate goals.